Specific features of photoprocesses in the dye merocyanine 540 and its complexes with water - Bazyl, Olga K. (Optics and spectroscopy)
The electronic structure and spectral-luminescence properties of the dye merocyanine 540 have been calculated within the framework of the semiempirical quantum-chemical method of partial neglect of differential overlap (PNDO) with spectroscopic parameterization. The trans and cis conformations of the molecule, as well as the trans-cis photoisomerization process, have been considered. The calculation has been performed for an isolated molecule of the merocyanine 540 and its complex with water. The results of the calculation have been compared with the experimental spectral-luminescence characteristics of the molecule in different solvents. It has been shown that there is a good agreement between the calculated and experimental spectra, the nature of the excited states, and photoprocesses. © 2016, Pleiades Publishing, Ltd.